Using Large-Scale Bibliometric Data in Higher Education Research. Methodological implications from three studies - Kwiek, Marek; Horta, Hugo; Powell, Justin J.W. (My University, 2024)
All fields of knowledge are challenged to adopt newer, more sophisticated methodologies to cope with growing complexity. Phenomena under study require further multidisciplinary and mixed methods collaborations to achieve expertise able to improve research strategies and practices. Furthermore, traditional methodological approaches face limits to their analytical reach. Here, we demonstrate opportunities from adopting newer, more sophisticated methodologies in the field of higher education (HE) research by comparing three case studies. We argue that such methods and data innovate the mapping and understanding of global HE. These studies uncover novel field characterizations, enabled via analysis of tens of thousands of HE authors and articles over several decades to assess how journal publication, topics, and levels of analysis (individual, organizational, and system) have evolved. Our results imply that to better understand the future of HE worldwide and to address growing challenges, newer methodological directions and data sources will be key to facilitate more comprehensive examinations of the globalizing field. However, our analysis also highlights the technical and learning challenges in implementing these methodologies; thus, we argue for the need to promote more sophisticated methodological training of current and future generations of HE researchers as well as strengthened collaborations across disciplinary, methodological, and cultural boundaries.
Keywords: Higher education research; bibliometrics; academic journals; international collaboration; large datasets